La sala multisensorial “de Snoezelen” para reducir los niveles de ansiedad en adultos mayores, del hogar de ancianos “Daniel Álvarez Sánchez” de la parroquia el Valle de la ciudad de Loja periodo octubre 2019 – septiembre 2020 - Iñahuazo Iñahuazo, Fernando Vinicio (2021)
This research work is a documentary review of scientific literature, focused on the analysis and study of the Snoezelen Multisensory Stimulation room and anxiety in older adults. The research design is of the documentary type in which information fromdocuments is collected through the search methods and strategies provided by the virtual library of the National University of Loja, as well as the information gathering techniques. The general objective is to contextualize bibliographically the importance of the multisensory stimulation room "Snoezelen" in older adults who present anxiety. For this, 44 investigations were selected, of which 40 correspond to digital books, scientific journals, websites and 4 theses. The results describe the theoretical foundation of the multisensory stimulation room, the description of anxiety levels in the elderly, the support of a plan of intervention activities for older adults with anxiety and the results obtained in theses focused on the topic. study.